Baby Einstein: Sweet Dreams, Mimi - Julie Aigner (Malasia Hyperion Book, 2004)
With delightful verse, real-life photos, and charming illustrations, this board book showcases all the wonderful sleepytime images that Mimi's mama recites as she tucks Mimi into bed. Full color.
Keywords: Board Book -- Board Book